2018
DOI: 10.11648/j.ijem.20180202.12
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review: Lean Manufacturing Assessment During the Time Period (2008-2017)

Abstract: The aim of this paper is to explore and evaluate previous work focusing on the relationship and links between Lean manufacturing and industrial work. This study reviews the literature on Lean Manufacturing Assessment (LMA) during the last decade; 2008-2017 and analyses the literature from different perspectives. This paper highlights various key words, scopes, objectives, case study, definitions, methodologies, tools and main results. A total of 126 research papers have been reviewed in this study to help the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…Structural equation modelling has become one of the most employed statistical methods in LM, OM (and management in general) research (Henao et al, 2019;Khalaf Albzeirat, 2018), thanks to its ability to explain multiple complex relationship among several non-directly measurable variables known as constructs (Hildebrandt and Temme, 2006). In business, OM, and industrial applications those constructs are usually used to represent measures related to strategy, performance, SCM, HRM, LM principles, and other parameters related to the operation (Abolhassani et al, 2016;Chatzoglou et al, 2018;Rais and Goedegebuure, 2009).…”
Section: Methodological Approachmentioning
confidence: 99%
“…Structural equation modelling has become one of the most employed statistical methods in LM, OM (and management in general) research (Henao et al, 2019;Khalaf Albzeirat, 2018), thanks to its ability to explain multiple complex relationship among several non-directly measurable variables known as constructs (Hildebrandt and Temme, 2006). In business, OM, and industrial applications those constructs are usually used to represent measures related to strategy, performance, SCM, HRM, LM principles, and other parameters related to the operation (Abolhassani et al, 2016;Chatzoglou et al, 2018;Rais and Goedegebuure, 2009).…”
Section: Methodological Approachmentioning
confidence: 99%
“…The structure consisted of measurements which reflected aims and LM strategies built for monitor and encourage lean behavior resulting in improved measurements. Few relevant studies reported on SMEs practicing lean methods are by Ali et al [4], Mehta et al [32], Graham et al [35], Cochran et al [37], Gangal et al [16]. Wagner et al [17] Chinese organizations, some others also used lean tools for SMEs in Brazil and more recently Marodin et al [44] employed Lean production methods with operational performance in automobile industries of Brazil.…”
Section: A Glimpse Of Lean Practices In Performance Evaluation Andmentioning
confidence: 99%
“…Lean Manufacturing is a set of functional tools for reducing waste and increasing productivity in industries through the implementation of a culture of continuous improvement in production systems and organizational activities [1]. In this mode, those functional tools are immersed in a context of continuous improvement that implies establishing indicators that can be measured to implement improvement actions in organizations in such a way that multiple research studies have been carried out that address this topic [2,3]. Lean Manufacturing is important for the improvement in production systems and requires continuous improvement to be effective [4].…”
Section: Introductionmentioning
confidence: 99%